Observation of trap-related phenomena in electrical performance of back-gated MoS2 field-effect transistors. (4th August 2020) - Mao, Yichen; Chang, Ailing; Xu, Pengpeng; Yu, Chunyu; Huang, Wei; Chen, Songyan; Wu, Zhengyun; Li, Cheng
Abstract: Trap-related phenomena in the electrical performance of back-gated mechanical exfoliated MoS2 field-effect transistors are investigated in terms of the super linear increase in the drain current under positive gate bias and the shift of transfer curves with gate voltage stress. The super linear increase in drain current is only observed for the MoS2 field-effect transistors in the electron accumulation regime under positive gate bias, which can be attributed to a trap-assisted tunneling effect with S vacancies at the contact interface between metal Ti and MoS2 . After thermal annealing of the devices in vacuum at 300 °C for 2 h, the almost complete metallization of Ti contacting with the MoS2 layer leads to the variation of the drain current relationship with drain voltage from a super linear to a linear increase, thus screening the efficacy of the mechanism of defect level assisted electron tunneling. The shift of transfer curves with gate voltage stress (denoted as hysteresis) is attributed to the defects near the interface between MoS2 and SiO2, which is slightly impacted by thermal annealing. The hump effect caused by parasitic transistors is also observed in back-gated mechanical exfoliated MoS2 field-effect transistors. These results further enrich the knowledge of the complex electrical characteristics of MoS2 field-effect transistors.